2012
DOI: 10.1136/tobaccocontrol-2012-050493
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure levels in outdoor hospitality venues: a qualitative and quantitative review of the research literature

Abstract: Objective This paper considers the evidence on whether outdoor secondhand smoke (SHS) is present in high enough levels of hospitality venues to potentially pose health risks, particularly among employees of such establishments. Data Sources Search strings in PubMed and Web of Science included combinations of environmental tobacco smoke, secondhand smoke, or passive smoke AND outdoor, yielding 217 and 5,199 results, respectively through June, 2012. Study Selection Sixteen studies were selected based on abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
4
21
1
Order By: Relevance
“…Nonetheless, nearly one-quarter of workers believed smoking should never be allowed in outdoor areas of workplaces, which is consistent with previous assessments of population-level attitudes toward smoke-free outdoor areas (Thomson, Wilson, & Edwards, 2009). Research suggests that outdoor SHS exposure can exceed acceptable air quality standards (Licht, Hyland, Travers, & Chapman, 2013), and smoking restrictions are increasingly being adopted in outdoor areas, including health care facilities, transport settings, universities, parks, beaches, and within specified distances from building entryways (ANRF, 2013c; Thomson et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, nearly one-quarter of workers believed smoking should never be allowed in outdoor areas of workplaces, which is consistent with previous assessments of population-level attitudes toward smoke-free outdoor areas (Thomson, Wilson, & Edwards, 2009). Research suggests that outdoor SHS exposure can exceed acceptable air quality standards (Licht, Hyland, Travers, & Chapman, 2013), and smoking restrictions are increasingly being adopted in outdoor areas, including health care facilities, transport settings, universities, parks, beaches, and within specified distances from building entryways (ANRF, 2013c; Thomson et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that non-smokers are exposed to SHS in outdoor areas where smoking is allowed (Licht, et al, 2013, Sureda, et al, 2013), and that SHS concentration is higher in outdoor locations such as bus stops, stadiums, bars and restaurants. In addition, when smoking is allowed in entrance areas, smoke-free indoor locations have high levels of SHS (Licht, et al, 2013, Sureda, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In a 2013 review I worked on, 17 the only studies we found were of real world or simulated outdoor exposure in crowded settings such as bar patios, beer gardens, and bus shelters. No studies looked at exposure in parks or on beaches-almost certainly because researchers with any knowledge of airborne exposures would appreciate that such exposures would be so small, dissipated, and transitory as to be of no concern.…”
Section: The Desire To Prevent Harm To Smokers and Othersmentioning
confidence: 99%